Foreign capital in the economy of Bosnia and Herzegovina (1918–1941) - Užičanin, Salkan (Historical Thought, 2025)
The author analyzes the participation of foreign capital in the economy of Bosnia and Herzegovina, as well as economic and political environment in which it operated, and its impact on economic activity of the country in the period from 1918 to 1941.